2015
DOI: 10.1002/ptr.5278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Total Flavones from Acanthopanax senticosus on L‐type Calcium Channels, Calcium Transient and Contractility in Rat Ventricular Myocytes

Abstract: Acanthopanax senticosus (Rupr. et Maxim.) Harms (AS), a traditional herbal medicine, has been widely used to treat ischemic heart disease. However, the underlying cellular mechanisms of its benefits to cardiac function remain unclear. The present study examined the effects of total flavones from AS (TFAS) on L-type Ca(2+) channel currents (ICa-L ) using the whole cell patch-clamp technique and on intracellular calcium ([Ca(2+) ]i ) handling and cell contractility in rat ventricular myocytes with the aid of a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…I Ca‐L was elicited under the steady‐state activation protocol. NiCl 2 (0.1 mM), a specific T‐type calcium channel blocker, had no influence on the currents, which showed that these currents were not T‐type Ca 2+ currents (Guan et al ., ). Beyond that, 0.01 mM nicardipin, a specific L‐type calcium channel blocker (Ren et al ., ), almost completely blocked the I Ca‐L , which showed that these currents were I Ca‐L in rat ventricular myocytes.…”
Section: Resultsmentioning
confidence: 97%
“…I Ca‐L was elicited under the steady‐state activation protocol. NiCl 2 (0.1 mM), a specific T‐type calcium channel blocker, had no influence on the currents, which showed that these currents were not T‐type Ca 2+ currents (Guan et al ., ). Beyond that, 0.01 mM nicardipin, a specific L‐type calcium channel blocker (Ren et al ., ), almost completely blocked the I Ca‐L , which showed that these currents were I Ca‐L in rat ventricular myocytes.…”
Section: Resultsmentioning
confidence: 97%
“…ASRE may directly relax vascular smooth muscle by inhibiting Ca 2+ channels or contraction pathways based on the result showing a reduction in vasoconstriction induced by an alphaadrenergic agonist and depolarization with high KCl in the presence of ASRE. Total flavones from A. senticosus reduce intracellular Ca 2+ by directly inhibiting L-type Ca 2+ channel currents in rat ventricular myocytes, resulting in a negative effect on myocardial contractility [18]. Furthermore, the possibility of hyperpolarization via K + channel opening cannot be excluded because Kwan et al (2004) suggested the involvement of EDHF in the vascular effects of ASRE; ASRE-induced relaxation in the Phenyl-precontracted rat aorta was completely reversed by 5 mM tetraethylammonium chloride [14].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicates that it mainly contains many flavonoids of which the chemical structures are characterized by quercetin, kaempferol, and isorhamnetin as aglycones linking with glycosyl groups [18, 19]. Many other researches have verified that flavonoids from Chinese herbs are effective on antiasthmatic, antitussive, and expectorant properties, for example, naringenin from Exocarpium Citri Grandis and total flavones from Acanthopanax senticosus [2629]. Moreover, plants from Elaeagnus are reported to have flavonoid constituents such as E. henryi , E. lanceolata , E. angustifolia, and E. bockii [8–10, 21].…”
Section: Discussionmentioning
confidence: 99%